(untitled) (Scientific journal of the Fergana State University, 2026)
The article examines the main methods and factors of using positive and negative words and expressions in various life situations, which reflect a person’s balanced attitude toward developing positive emotions that influence the human brain. A significant part of the specific features of words and their associative meanings is related to speech activity, which makes it possible to identify the influence of speech on perception and expression in dialogue. Often, the direct meaning of a word or phrase is not used; instead, depending on characterological features, details are employed in depicting reality, which encourages progress in the sphere of emotional well-being. The emotional characteristics of words determine their impact on people — in any dialogue, each remark or utterance performs a certain function, transforming positive words or expressions and giving them unique expressiveness. In the context of active information exchange between cultures, languages are changing rapidly; however, new challenges also arise, such as preserving national identity and linguistic culture. These changes, driven by globalization, affect all layers of society and open new horizons, including in the linguistic sphere..